Going Beyond Average Response: Modeling Portuguese Residential Water Demand with Quantile Regression - Monteiro, H.; Cardoso, M.; Figueiredo, M. C. T. (8.º Congresso Ibérico de Gestão e Planeamento da Água, 2013)
Recent research has pointed out that price-elasticity of residential water demand may not be constant throughout the consumption distribution. If this is so, knowing the price-elasticity for the average of the sample or population of consumers is insufficient to predict the possible impacts of a price change. We use quantile regression to estimate the impacts that different relevant explanatory variables (including price) may have on water consumption for different consumption quantiles in order to get a more accurate picture of the full impact of price changes. Our results for a sample of Portuguese households facing increasing-block tariffs show that the relevant variables that have been used for decades to estimate the residential water demand may have different impacts for consumers with different consumption levels. Because this is also true for the consumers’ response to price a rethinking of how the impact of a price change is computed is called for.